2019
DOI: 10.3390/ma12040672
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Corrosion Behavior of Atomic Layer Deposited Al2O3/TiO2 Nanolaminate Thin Films on Copper in 0.1 M NaCl

Abstract: Fifty nanometers of Al2O3 and TiO2 nanolaminate thin films deposited by atomic layer deposition (ALD) were investigated for protection of copper in 0.1 M NaCl using electrochemical techniques. Coated samples showed increases in polarization resistance over uncoated copper, up to 12 MΩ-cm2, as measured by impedance spectroscopy. Over a 72-h immersion period, impedance of the titania-heavy films was found to be the most stable, as the alumina films experienced degradation after less than 24 h, regardless of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 102 publications
1
22
0
Order By: Relevance
“…In the literature, different corrosion current densities were reported. 31 , 89 , 90 For example, corrosion current densities of 8.3×10 –7 A cm –2 and 3×10 –8 A cm –2 were found for 29 nm thick Al 2 O 3 films on copper by Daubert et al and Chai et al, respectively. 36 , 38 Indeed, Mirhashemihaghighi et al .…”
Section: Resultsmentioning
confidence: 98%
“…In the literature, different corrosion current densities were reported. 31 , 89 , 90 For example, corrosion current densities of 8.3×10 –7 A cm –2 and 3×10 –8 A cm –2 were found for 29 nm thick Al 2 O 3 films on copper by Daubert et al and Chai et al, respectively. 36 , 38 Indeed, Mirhashemihaghighi et al .…”
Section: Resultsmentioning
confidence: 98%
“…Larger thicknesses could further improve the corrosion resistance as it was previously reported in the context of flat metal surfaces. 52,55,57,58 However, thicknesses above 15 nm are not appropriate for plasmonic applications which require nanoscale features and short distances to the metal film so as to maximize the electromagnetic field enhancement. 1 On the lower side, we found that a 5 nm thickness did not provide a sufficient improvement in the photocorrosion protection.…”
Section: Resultsmentioning
confidence: 99%
“…Atomic layer deposition (ALD) and plasmaenhanced chemical vapor deposition (PECVD) of thin inert layers of metal oxides offer powerful alternative approaches for corrosion protection owing to their ability to deposit dense layers of oxide materials with controlled nanometer thickness and conformal coating at the nanoscale. 50 Alumina (Al2O3), [51][52][53] titania (TiO2) [54][55][56] and hafnia (HfO2) 57,58 are commonly used to protect flat metal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these properties include high electrical and thermal conductivity and high reflectivity [1,2]. Aluminum owes high corrosion resistance because of the tenacious oxide film (Al 2 O 3 ) which occurs naturally on its surface [3][4][5]. Due to high reflectivity and thermal conductivity, aluminum requires high laser power to melt [6,7].…”
Section: Introductionmentioning
confidence: 99%